2018
DOI: 10.1016/j.dib.2018.09.132
|View full text |Cite
|
Sign up to set email alerts
|

Species characteristics of felids and canids, and the number of articles published for each species between 2013 and 2017

Abstract: The data presented are related to the research article entitled “Biases in wildlife and conservation research, using felids and canids as a case study” available at https://doi.org/10.1016/j.gecco.2018.e00423. This data article lists species characteristics of two families of the order Carnivora, the Felidae and Canidae, and quantitatively categorizes research output for each species. The species characteristics that were included in the dataset are body size (in kg), geographic range size, IUCN species status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…These canids have a wide distribution across South and Central America but remain rare and under-studied among Neotropic carnivore mammals (Leite-Pitman & Beisegel 2013). For example, a 2018 review revealed that no new literature on A. microtis appeared between 2013 and 2017 (Tensen 2018). Despite their classification as Near Threatened by the International Union for Conservation of Nature (Leite-Pitman & Williams 2011), more recent research suggests that A. microtis may be at even higher risk than currently acknowledged (Rocha et al 2020).…”
mentioning
confidence: 99%
“…These canids have a wide distribution across South and Central America but remain rare and under-studied among Neotropic carnivore mammals (Leite-Pitman & Beisegel 2013). For example, a 2018 review revealed that no new literature on A. microtis appeared between 2013 and 2017 (Tensen 2018). Despite their classification as Near Threatened by the International Union for Conservation of Nature (Leite-Pitman & Williams 2011), more recent research suggests that A. microtis may be at even higher risk than currently acknowledged (Rocha et al 2020).…”
mentioning
confidence: 99%